Random Number Generator based on Ring Oscillators for IoT applications - Mendes, Pedro Miguel Nunes (2018)
Since the beginning of times that human beings were presented with the difficult of protecting their data. In all wars, cryptographic systems where essential to wining. Nowadays, fighting global terrorism makes cryptography of paramount importance in communication and security of critical systems. Cryptographic methods present a real challenge, so hard that it is as difficult to create as it is to crack. Since the first appearances of Integrated Circuits, methods have been created to protect the data on them, the same happened when the first networks appeared and nowadays we still face the same challenge. Centuries have passed and the definition of the random word still creates confusion when trying to define it. This thesis proposes a random generation method which proved to be effective according to worldwide standards with the new emerging technologies of the IoT in mind. A True Random Number Generator (TRNG) based on ring oscillators, implemented in a Field Programmable Gate Array (FPGA) platform is proposed and evaluated. Based on some new concepts on ring oscillators, jitter noise was analysed and used as a main noise source to create randomness. The main aim of this project was to investigate and develop of a secure system that met the international requirements for IoT purposes.